Genetic enhancement of early and extra-early maturing maize for tolerance to low-soil nitrogen in sub-Saharan Africa - Badu-Apraku, B.; Fakorede, M.A.B.; Annor, B.; Adu, G.B.; Obeng-Bio, E.; Abu, P.; Bhadmus, O.A.; Nelimor, C. (Hapres, 2023)
To increase and improve food crop production and crop management for sustainable agricultural development, the Maize Improvement Program (MIP) of the International Institute of Tropical Agriculture (IITA) has, in partnership with national and international organizations, focused attention on the genetic improvement of maize (Zea mays L.) for tolerance/resistance to abiotic and biotic stresses constraining maize grain production. One of the abiotic stresses into which new technologies have been established for crop protection and sustainable natural resource management is low soil nitrogen (N). Nitrogen, an important plant nutrient required for growth and productivity, is not readily available and little quantity or none is applied by farmers for maize production. Because of long periods of bush fallow, the absence of N was not noticeable at the initial stages of maize production in West and Central Africa (WCA). However, with the fallow period gradually reducing and totally disappearing, it has become imperative for external supply of N in maize production. Taking a cue from the International Maize and Wheat Improvement Centre (CIMMYT), IITA has been breeding low-N tolerant maize and several low-N-tolerant maize varieties and hybrids are now available to farmers. Reviewed in this manuscript are the efforts used to develop low-N tolerant early and extra-early maturing maize by the MIP of IITA. The review covers the objectives, methodology, and output of the research, including the genetics of tolerance, ongoing conventional and molecular approaches, and the gaps that new research could fill.